2017
DOI: 10.1186/s13756-017-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

MRSA decolonization failure—are biofilms the missing link?

Abstract: BackgroundDevice-associated infections due to biofilm-producing methicillin-resistant Staphylococcus aureus (MRSA) have been recently associated with the failure of antibiotic treatment and decolonization measures. The goal of our study was to evaluate the extent to which the formation of biofilms influenced the efficacy of topical decolonization agents or disinfectants such as mupirocin (MUP), octenidine (OCT), chlorhexidine (CHG), polyhexanide (POL), and chloroxylenol (CLO).MethodsBacterial killing in biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(27 reference statements)
0
14
0
3
Order By: Relevance
“…Other authors have reported a high level of simultaneous mupirocin resistance with other antibiotics in association with a more frequent MRSA colonization. [4][5][6][7][8][9][10][11][12] Therefore, mupirocin is recommended as a first-line treatment for impetigo in patients with a limited number of lesions, especially considering MRSA local resistance patterns as per the 2014 guidelines of the Infectious Diseases Society of America. 3 In a children's hospital in the USA, mupirocin resistance was detected in 14.7 % of S. aureus isolates in association with recurrent skin and soft tissue infections, which was higher than the rate observed in other community studies conducted in children (1.8 %).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have reported a high level of simultaneous mupirocin resistance with other antibiotics in association with a more frequent MRSA colonization. [4][5][6][7][8][9][10][11][12] Therefore, mupirocin is recommended as a first-line treatment for impetigo in patients with a limited number of lesions, especially considering MRSA local resistance patterns as per the 2014 guidelines of the Infectious Diseases Society of America. 3 In a children's hospital in the USA, mupirocin resistance was detected in 14.7 % of S. aureus isolates in association with recurrent skin and soft tissue infections, which was higher than the rate observed in other community studies conducted in children (1.8 %).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the possible correlation between mupirocin resistance in MRSA and its ability to form biofilm, other authors have reported biofilm-forming MUP-R-MRSA strains isolated in swabs from infected wounds collected after a surgery. 12 It has been suggested that biofilm formation may play a role in mupirocin resistance in the overall population of hospitalized patients. 11,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otros autores reportaron un alto nivel de resistencias simultáneas de la mupirocina con otros antibióticos asociado con una recolonización más habitual por SARM. [4][5][6][7][8][9][10][11][12] Por ello, la mupirocina se recomienda como tratamiento de primera línea para el impétigo en los pacientes con un número limitado de lesiones y, sobre todo, teniendo en cuenta los patrones locales de resistencia del SARM según las directrices de 2014 de la Sociedad de Enfermedades Infecciosas. 3 En un hospital de niños de EE.…”
Section: Discussionunclassified
“…Con respecto a la posible correlación entre la resistencia a la mupirocina en los aislados de SARM y su capacidad para formar el biofilm, otros autores reportaron cepas de SARM-R-MUP aisladas a través de hisopados de heridas infectadas tomados posoperación, que eran productoras de biofilm. 12 Se ha sugerido que la formación de biofilm puede jugar un papel en la resistencia a la mupirocina entre las poblaciones de pacientes hospitalizados en general. 11,12…”
Section: Discussionunclassified